1997
DOI: 10.1046/j.1365-2265.1997.1610972.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth response and levels of growth factors after two years growth hormone treatment are similar for a once and twice daily injection regimen in girls with Turner syndrome

Abstract: The present growth data are in conformity with the data of the earlier 24-hour GH profiles. The growth response and plasma levels of growth related factors after 2 years GH on a total dose of 6 IU/m2/day in combination with low-dose oestrogens were not significantly different between the once daily and the twice daily GH injection regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…Our final height data are in line with the two year results 23. The growth response after two years’ GH on a total daily dose of 6 IU/m 2 in combination with 0.05 μg ethinyl oestradiol/kg/day was not significantly different between the two GH injection regimens.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our final height data are in line with the two year results 23. The growth response after two years’ GH on a total daily dose of 6 IU/m 2 in combination with 0.05 μg ethinyl oestradiol/kg/day was not significantly different between the two GH injection regimens.…”
Section: Discussionsupporting
confidence: 88%
“…As described in a previous paper,23 at baseline, there were no relevant differences between the two groups for any of the variables. Before treatment, the mean chronological age, bone age, and HSDS CA values of the girls in the twice daily group were slightly (not significantly) higher compared with those in the once daily group.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The ratio IGF-I/IGFBP-3 increases during GH treatment (35), and it is high in acromegaly (6). Furthermore, we have previously found that the molar ratio of IGF-I to IGFBP-3 was decreased in adult GHD patients (10).…”
Section: Figurementioning
confidence: 99%
“…At a dose of 0.14 IU/kg per day a first year increase in growth velocity of about 4 cm above baseline level was found in a trial of 65 girls with Turner syndrome [18]. Another, controlled study of 232 Turner subjects reported increases in first year growth velocity of less than 3 cm/year compared with that of a control group and without a significant difference between GH doses of 0.12 or 0.15 IU/kg per day [19].…”
Section: Comparison With Short-term Effect Of Gh Treatment In Turner mentioning
confidence: 99%